Synchronous Spinal Tumor: A Rare Case Report (TAJ: Journal of Teachers Association, 2009)
Most meningiomas of the spinal cord are benign and arise from arachnoid membrane. We are reporting synchronous two meningiomas, one at T10-11 and another at L1 level in the same patient. doi: 10.3329/taj.v17i2.3458   TAJ 2004; 17(2): 108-109